Chromosomal Polymorphism in the Sporothrix schenckii Complex - Sasaki, Alexandre A.; Fernandes, Geisa F.; Rodrigues, Anderson M.; Lima, Fábio M.; Marini, Marjorie M.; dos S. Feitosa, Luciano; de Melo Teixeira, Marcus; Felipe, Maria Sueli Soares; da Silveira, José Franco; de Camargo, Zoilo P. (PLOS ONE, 2014)
Sporotrichosis is a polymorphic disease caused by a complex of thermodimorphic fungi including S. brasiliensis, S. schenckii sensu stricto (s. str.), S. globosa and S. luriei. Humans and animals can acquire the disease through traumatic inoculation of propagules into the subcutaneous tissue. Despite the importance of sporotrichosis as a disease that can take epidemic proportions there are just a few studies dealing with genetic polymorphisms and genomic architecture of these pathogens. The main objective of this study was to investigate chromosomal polymorphisms and genomic organization among different isolates in the S. schenckii complex. We used pulsed field gel electrophoresis (PFGE) to separate chromosomal fragments of isolated DNA, followed by probe hybridization. Nine loci (β-tubulin, calmodulin, catalase, chitin synthase 1, Internal Transcribed Spacer, Pho85 cyclin-dependent kinase, protein kinase C Ss-2, G protein α subunit and topoisomerase II) were mapped onto chromosomal bands of Brazilian isolates of S. schenckii s. str. and S. brasiliensis. Our results revealed the presence of intra and interspecies polymorphisms in chromosome number and size. The gene hybridization analysis showed that closely related species in phylogenetic analysis had similar genetic organizations, mostly due to identification of synteny groups in chromosomal bands of similar sizes. Our results bring new insights into the genetic diversity and genome organization among pathogenic species in the Sporothrix schenckii complex.